Edukasi Kesiapsiagaan Bencana Alam di Desa Karangbanjar, Kecamatan Bojongsari, Kabupaten Purbalingga - Ika Maulita; Destin Alfianika Maharani; Siti Nasiroh; Melia Dwi Renovriska; Ayu Sitanini (Fakultas Sains Dan Teknologi, Universitas Raden Rahmat Malang, 2024)
Disaster preparedness training in Karangbanjar Village faces the challenge of increasing community understanding and awareness of disasters. The purpose of this activity is to strengthen the adaptive capacity and preparedness of the community through education and practical simulations. Implementation methods include counseling, practical training, and disaster simulation. The results of the activity showed a significant increase in participants' understanding, as evidenced by the pre-test and post-test results which showed a statistically significant increase in understanding. Evaluation of participants' progress, as measured through the pre-test and post-test, revealed a substantial increase in understanding with the average score increasing from 5.9 to 7.1. This improvement, which represents an overall increase in understanding of 34.61%, was statistically validated through a paired t-test, where the results showed a statistically significant difference between the pretest and post-test scores with a test statistic of -2.708 and a p-value of 0.0112. The program successfully increased community awareness and proactivity in facing disasters, proving the importance of disaster preparedness education in building resilient communities.